Utilización de la thiourea como agente alternativo para lixiviar minerales altamente refractarios en la recuperación de oro. - Meza Carranza, Erix Heybilder (2012)
In this research gold recovery was performed by the method of acid leaching with constant stirring from a highly refractory ore from the metallurgical laboratory of the National University of Trujillo, Department of Metallurgical Engineering (Law 2.84 oz Au / TM); the independent variables was evaluated as the concentration of thiourea solution and stirring time. The particle size of the refractory ore was 100% solids and mesh No. 200 and the tests were performed in the laboratory mineral processing metallurgical engineering department. In the experimental part were performed to test turmoil in bottle for 72 hours of constant agitation and chemical composition of refractory ore, by analysis on a dry basis and atomic absorption and student test for a single sample of data statistical analysis was performed and is the most significant variables in gold recovery for this research, is the concentration of thiourea solution and stirring time. In addition, the best result was obtained gold recovery when they met 72 hours optimum reaching an agitation gold recovery up to 71.73% Au. It was shown that this acid leaching method with constant stirring in the presence of ferric sulfate is viable to process highly refractory ores.